Is the relationship between men's age at first birth and midlife health changing? Evidence from two British cohorts. (August 2019) - Einiö, Elina; Goisis, Alice; Myrskylä, Mikko
Abstract: Becoming a father, particularly for the first time, is a central transition in men's lives, and whether this transition takes place early or later in life may have important ramifications on the whole later life course. Previous research has shown that men who father their first child early in life have poorer later-life health than men who postpone having children. However, it is not known how selection by cognitive ability and other childhood characteristics confound the association between the timing of fatherhood and later-life health, or how the association is changing over time as parenthood is postponed to an older age. We investigate the association between men's age at the birth of their first child and midlife self-rated health in two British cohorts born in 1958 and 1970. The study employs logit models. Relative to men who had their first child when they were between 25 and 29 years old, men who had their first child before the age of 20 have the poorest health, followed by men who had a child when they were 20–24 years old. This result was observed in both cohorts. Childhood cognitive ability, which previous research has not analyzed, strongly contributed to this association, and to a greater extent than other childhood characteristics. For the 1970 cohort, those who became fathers at age 35 or older had the best health. This advantage was not found for the 1958 cohort. These findings suggest that the relationship between young age at fatherhood and midlife health is strongly confounded by cognitive ability, and that in recent cohorts a new pattern of advantage among older fathers has emerged. Highlights: Early fatherhood shows associations with poorer self-rated health in midlife. Childhood cognitive ability strongly confounds this association. First-time fathers aged 35 years or older have the best health in the 1970 cohort. A similar health advantage in older fathers is not found in the 1958 cohort.